The Influence Of Work Ability And Public Perception On Employee Performance Through The Quality Of Health Services In Community Health Center In Ternate City - Ferial Ferial (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
The influence of work ability and public perception on employee performance through the quality of health services at the Community Health Center in Ternate City, supervised by Jamaluddin B. Ilyas and Tajuddin Malik, The purpose of the study was to determine the influence of work ability and public perception on em-ployee performance through the quality of health services at the Community Health Center in Ternate City. The research method used is a quantitative analysis method with data collection through the distribution of observations, interviews, questionnaires and document reviews then processed in the form of a frequency dis-tribution table. The sampling technique uses proportional samples. The population in this study were all patients who were treated at the Community Health Center in Ternate City, the total sample was 100 respondents. The results of the study indicate that the variables Work ability (X1), Community perception variable (X2), Health service quality variable (Z1), Employee performance variable (Y1) have a direct and indirect influence in im-proving the quality of health services and employee performance at the Community Health Center in Ternate City.